2016
DOI: 10.1097/iop.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Following Nasolacrimal Duct Probing

Abstract: Nasolacrimal duct probing does not induce bacteremia in routine CNLDO cases unless there is an associated acute dacryocystitis. Preoperative antibiotic prophylaxis is perhaps not needed for systemically healthy CNLDO patients without an acute dacryocystitis. However, with regards to infantile acute dacryocystitis, further evidence is needed to formulate guidelines on additional preoperative antibiotic prophylaxis other than the routine treatment of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…H. influenzae and S. pneumoniae were reported to be prevalent bacteria in CNLDO patients with a wider range of age (Table 3 ), both pathogens can induce bacteremia after lacrimal probing [ 29 , 30 ], and S. pneumoniae can cause severe endophthalmitis following glaucoma or cataract surgeries [ 31 , 32 ]. Neisseriae species are part of the normal flora in respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…H. influenzae and S. pneumoniae were reported to be prevalent bacteria in CNLDO patients with a wider range of age (Table 3 ), both pathogens can induce bacteremia after lacrimal probing [ 29 , 30 ], and S. pneumoniae can cause severe endophthalmitis following glaucoma or cataract surgeries [ 31 , 32 ]. Neisseriae species are part of the normal flora in respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…12,28 Baskin et al 4 showed bacteremia in 22.7% of infants and that antibiotic administration 24 hours before probing reduced the chances of repeat probing. Ganguly et al, 29 studied bacteremia in paediatric patients undergoing probing. They recommended that routine probing does not require antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%